Bureaucratic rationality, political will, and state capacity: MGNREGS in undivided Andhra Pradesh - Mukherji, Rahul; Jha, Himanshu (Economic & political weekly, 2017)
The successful implementation of the Mahatma Gandhi National Rural Employment Guarantee Scheme in undivided Andhra Pradesh underlines the triumph of citizen formation over patron-client politics, aided by a democratic politics. This article argues that its success in Andhra Pradesh depended heavily on how the ideas within the rural development bureaucracy interacted with the political executive. This synergy engendered a state’s capacity to insulate a committed bureaucracy from powerful farmers and construction companies who had a clear interest in thwarting the programme. Elections can in a democracy elevate citizen concern over particularistic populism, when political will is matched by ideational conviction in the bureaucracy.
Gesehen am 15.12.2017